2011
DOI: 10.1159/000331709
|View full text |Cite
|
Sign up to set email alerts
|

The Cardioprotective Effect of Brief Acidic Reperfusion after Ischemia in Perfused Rat Hearts is not Mimicked by Inhibition of the Na<sup>+</sup>/H<sup>+</sup> Exchanger NHE1

Abstract: Background: Ischemic postconditioning (PostC), i.e. brief ischemia-reperfusion cycles before full reperfusion, is protective against cardiac ischemia/reperfusion (I/R) injury. Inhibition of the Na+/H+ exchanger NHE1 and delayed intracellular pH-normalization have been proposed to underlie protection by PostC. Methods and Results: We used Langendorff perfused rat hearts exposed to 35 min global ischemia to show that 15 min acidic (pH 6.5) treatment at onset of reperfusion decreased infarct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…We noted that the death of ouabain-treated MDCK cells was completely abolished by acidification of medium from pH 7.4 to 7.0, i.e., under conditions when pH i was decreased from ϳ7.2 to 6.9 (3). This observation contrasted with the lack of any impact of acidification on the appearance of necrotic and apoptotic markers in atrial cardiomyocytes subjected to ischemia-reperfusion (8). Surprisingly, almost complete Na/K pump inhibition and fullscale increase of the [Na ϩ ] i /[K ϩ ] i ratio evoked by K ϩ -free medium did not affect the survival of MDCK cells (36,105).…”
Section: [Na ϩ ] I /[K ϩ ] I -Independent Death Signaling Triggered Bmentioning
confidence: 80%
“…We noted that the death of ouabain-treated MDCK cells was completely abolished by acidification of medium from pH 7.4 to 7.0, i.e., under conditions when pH i was decreased from ϳ7.2 to 6.9 (3). This observation contrasted with the lack of any impact of acidification on the appearance of necrotic and apoptotic markers in atrial cardiomyocytes subjected to ischemia-reperfusion (8). Surprisingly, almost complete Na/K pump inhibition and fullscale increase of the [Na ϩ ] i /[K ϩ ] i ratio evoked by K ϩ -free medium did not affect the survival of MDCK cells (36,105).…”
Section: [Na ϩ ] I /[K ϩ ] I -Independent Death Signaling Triggered Bmentioning
confidence: 80%
“…We and others have demonstrated that Cx-II inhibition at the start of reperfusion is protective in animal and perfused organ models of IR injury [ 15 , [27] , [28] , [29] , [30] ]. In addition, it is known that prolongation of ischemic tissue acidosis into the reperfusion period can improve recovery from IR injury [ 31 , 32 ]. While the exact protective mechanism of “acid post-conditioning” is poorly characterized, it may involve a recently described pH sensor on the PT pore [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Osmolyte transporters counteract cell shrinkage, which is known to parallel and facilitate suicidal cell death [51,52,53,54,55,56,57,58,59,60]. BGT1 participates in the cellular accumulation of organic osmolytes [9,10], which are well known to foster cell survival [8,26].…”
Section: Discussionmentioning
confidence: 99%